2015
DOI: 10.1371/journal.pone.0139611
|View full text |Cite|
|
Sign up to set email alerts
|

Collagen Sequence Analysis of the Extinct Giant Ground Sloths Lestodon and Megatherium

Abstract: For over 200 years, fossils of bizarre extinct creatures have been described from the Americas that have ranged from giant ground sloths to the ‘native’ South American ungulates, groups of mammals that evolved in relative isolation on South America. Ground sloths belong to the South American xenarthrans, a group with modern although morphologically and ecologically very different representatives (anteaters, armadillos and sloths), which has been proposed to be one of the four main eutherian clades. Recently, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 38 publications
1
20
0
3
Order By: Relevance
“…Using this information, previously published sequence information as well as fingerprints, these markers were identified for all taxa in this study with novel ones confirmed through tandem sequencing where possible. Tandem mass spectra were acquired through the use of an LCOrbitrap Elite mass spectrometer following Wadsworth & Buckley (2014) and searches using Mascot with a local database (Buckley et al 2015) improved with select additional sequences obtained from a protein BLAST search (Table S1), particularly for red fox, beaver and walrus (the latter for improved understanding of peptide marker labels). Error tolerant searches (5 ppm and 0.5 Da error tolerances on precursor and tandem spectra, respectively) were used to confirm proposed peptide markers as homologous (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Using this information, previously published sequence information as well as fingerprints, these markers were identified for all taxa in this study with novel ones confirmed through tandem sequencing where possible. Tandem mass spectra were acquired through the use of an LCOrbitrap Elite mass spectrometer following Wadsworth & Buckley (2014) and searches using Mascot with a local database (Buckley et al 2015) improved with select additional sequences obtained from a protein BLAST search (Table S1), particularly for red fox, beaver and walrus (the latter for improved understanding of peptide marker labels). Error tolerant searches (5 ppm and 0.5 Da error tolerances on precursor and tandem spectra, respectively) were used to confirm proposed peptide markers as homologous (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Peptide homology was assisted through Error Tolerant searches using Mascot (e.g. Figs S2-S7) against the SwissProt database (Buckley et al, 2015).…”
Section: Protein Extraction and Collagen Fingerprintingmentioning
confidence: 99%
“…La condición de grupo natural de los Xenarthra está claramente sustentada, en tanto que los caracteres tradicionalmente utilizados para definir las sinapomorfías clásicas de este grupo son morfológicos, basados principalmente en elementos esqueletarios y dentarios (Engelmann, 1985;Gaudin, 1995Gaudin, , 1999Gaudin, , 2004Gaudin et al, 1996, McDonald, 2003Rose et al, 2005;Gaudin & McDonald, 2008). Asimismo los estudios filogenéticos con base en datos moleculares también sostienen que este es un grupo monofilético (de Jong et al, 1985;Sarich, 1985;Delsuc et al, 2001Delsuc et al, , 2002Delsuc et al, , 2003Madsen et al, 2001;Murphy et al, 2001); en años recientes se publicaron análisis que incluyen algunos de los taxones aquí analizados (tardígrados fósiles y gliptodóntidos), basados en ADN antiguo (ADNa) y colágeno (Buckley et al, 2015;Delsuc et al, 2016;Slater et al, 2016).…”
Section: Introductionunclassified